MSME Sustainability Strategy Through the Application of Digital Marketing and Product Innovation in the VUCA Era: A Study of SMEs in Sukabumi City - Rizky Maulana; Alhidayatullah Alhidayatullah; Sandi Setiadi (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the influence of digital marketing and product innovation on the sustainability of food MSMEs in Sukabumi City in facing the challenges of the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. The research method used a quantitative approach with Structural Equation Modeling – Partial Least Square (SEM-PLS) analysis technique through the SmartPLS 4.0 application. The research sample consisted of 100 food MSME actors selected using purposive sampling. The results showed that digital marketing had a significant negative effect on business sustainability. This indicates that the implementation of digital marketing in MSMEs is not yet optimal and still requires more appropriate strategies for its utilization. Conversely, product innovation was found to have a positive and dominant effect on business sustainability. This means that the higher the MSME's ability to innovate, the greater their chances of surviving and growing. The R-Square value of 0.955 shows that digital marketing and product innovation can explain 95.5% of MSME business sustainability, while the rest is influenced by other factors outside the model. In conclusion, MSME business sustainability is largely determined by the ability to innovate, while digital marketing will only be effective if supported by products that are relevant, high-quality, and in line with consumer needs. This study contributes theoretically to the development of literature on SME digital adaptation in the context of VUCA, as well as practically by providing recommendations for SMEs, the government, and supporting institutions to enhance product innovation while optimizing digital marketing strategies in a sustainable manner.